Significance of walkability in the context of terrace row houses in Malaysia : an ethnographic approach - Nazem, Sara (2013)
Walking is an excellent physical exercise. But it can contribute more than that. Pedestrian activities create social interaction in urban environments. Therefore walkability can play a significant role in Urban Design. Concentrating on residential neighborhoods, walkability can also reduce dependence on cars at least for shorter distances, and therefore contribute to economic and environmental sustainability as well. However, in a primarily car-dependent street network, walkability in residential neighborhoods has been neglected in Malaysia, especially in the terrace row housing estates, which is the most popular type of housing estates in the country. As a consequence, social interaction between neighbors has become extinct, which not only started depriving the neighborhoods from its liveliness, but also threatened the much needed security in such urban environment. Therefore, a study of walkability in terrace row housing states in Malaysia seems to be very much relevant and significant. This research aimed to investigate walkability of terrace row housing estates under three objectives. It tried to anticipate the degree of walkability, to identify the major problems related to walkability, and to provide suggestions for a pedestrian friendly street network inside such estates. The study adopted the qualitative approach, with ethnography as the research method. The researcher, as a participant observer, collected the data through intensive and informal interviews with residents of such neighborhoods. Identifying street network as the key urban element for walkability, and its connectivity with different facilities inside the neighborhoods as the benchmark to measure walkability, the sample of five housing estates was selected on the basis of four parameters. These are the existence of footpaths, intensity of traffic flow, connection from house to common facilities, and existence of guarded community. After collecting the data in the form of vignettes, several themes were derived through immersion. After verifying them through triangulation and peer review, the number of themes was later reduced to domains that represented the findings of the research. It showed that the residents indeed feel the necessity of more walkability inside neighborhoods, and the several steps should be immediately adopted with regards to the street network in order to develop walkability.